DETERMINANTS OF TAX AGGRESSIVITY IN REGISTERED PHARMACEUTICAL SECTOR COMPANIES IN INDONESIA STOCK EXCHANGE MODERATED BY PROFITABILITY - Rini Ariyani; Syafrida Hani; Irfan (SEAN Institute, 2023)
This study aims to determine, test, and analyze the effect of liquidity, leverage and capital intensity on tax aggressiveness moderated by profitability in pharmaceutical sector companies listed on the Indonesia Stock Exchange. This study uses quantitative methods with an associative approach and documented data collection by collecting, recording, reviewing and analyzing secondary data in the form of financial statements of manufacturing companies in the pharmaceutical sub-sector from 2016-2021. This study took 42 samples using purposive sampling method. The data analysis technique used is descriptive statistics which is used to explain the description of the data from all variables and also multiple linear regression analysis and the Moderated Regression Analysis (MRA) test. The results of this study indicate that liquidity and capital intensity have no effect on tax aggressiveness. And leverage has an effect on tax aggressiveness. Profitability is able to moderate (strengthen) the effect of liquidity, leverage and capital intensity on tax aggressiveness.